Asymmetric Organocatalytic Synthesis of 2-Oxindole Based Heterocycle Precursors - Tanyeli, Cihangir (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
Recent literature on the bioactivity of isatin (indoline-2,3-dione) derivatives triggered organic chemists to make use of the unique potential of isatin in asymmetric organocatalytic synthesis. Due to the extensive presence of the 2-oxindole skeleton, especially spiro-fused cycles, in many natural products, they drew special interest in medicinal chemistry and agrochemistry. Due to the highly reactive prochiral carbonyl group, isatins are potent precursors for the synthesis of 3,3-disubstituted spirooxindoles. Direct nucleophilic addition to isatin-derived ketimines is one of the straightforward approaches leading to α-chiral amines, which are frequent subunits of pharmaceuticals and agrochemicals. Asymmetric organocatalytic synthesis offers a facile and environmentally benign reaction process with good selectivity. The remarkable advantages of cooperative activation of substrates via bifunctional organocatalysts bearing H-bond donor components such as urea, thiourea and squaramide are indispensable. Modulation of sterically encumbered units such as 1-adamantyl, 2-adamantyl and t-butyl in the structure of the organocatalyst reveals distinct changes in stereoselectivity.